KEMAMPUAN DEGRADASI RESIDU FUNGISIDA MANKOZEB OLEH Trichoderma harzianum DAN Trichoderma viride - Risya Rosyida; Suryana; Indah Sri Lestari; Riska Sukmawati (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2026)
[THE POTENTIAL OF Trichoderma harzianum AND Trichoderma viride AS BIODEGRADATION AGENTS FOR FUNGICIDE RESIDUES CONTAINING THE ACTIVE INGREDIENT MANCOZEB]. Repeated use of fungicides containing the active ingredient mancozeb has the potential to leave residues in agricultural environments and suppress the activity of non-target soil microorganisms. This study aimed to assess the potential and determine the differences between the fungi Trichoderma viride and Trichoderma harzianum in degrading fungicides containing the active ingredient mancozeb in vitro. The study was conducted at the Plant Pathology Laboratory and the Pesticide Toxicology Laboratory, Department of Plant Pests and Diseases, Faculty of Agriculture, Brawijaya University, from May 13 to October 30, 2025. The study employed an experimental design using a completely randomized design. Isolates of T. harzianum and T. viride were purified on PDA medium,identified macroscopically and microscopically, and then propagated on PDB medium. The test was conducted by growing the isolates on PDB medium containing mancozeb at concentrations of 0; 0.5; 1; 1.5; and 2 g/L for 10 days. The parameters observed included Trichoderma biomass and the colony diameter of Colletotrichum gloeosporioides in the bioassay as indicators of residue toxicity. The data were analyzed using ANOVA, followed by a 5% DMRT. The results showed that increasing mancozeb concentration reduced the biomass of both fungi but did not completely inhibit their growth. T. viride produced 0.40 g of biomass in the control and 0.21 g at 2 g/L, while T. harzianum produced 0.48 g in the control and 0.23 g at 2 g/L. The bioassay test showed an increase in the diameter of C. gloeosporioides on media treated with Trichoderma compared to those without Trichoderma. The highest difference in diameter occurred at a concentration of 2 g/L, namely 42.5% for T. viride and 43.5% for T. harzianum. Thus, both Trichoderma species are tolerant to mancozeb and have the potential to reduce its residual toxicity, with a tendency for higher efficacy in T. harzianum under limited in vitro testing conditions.